The effect of (±)-CP-101,606, an NMDA receptor NR2B subunit selective antagonist, in the Morris watermaze - Guscott, Martin R.; Clarke, Hannah F.; Murray, Fraser; Grimwood, Sarah; Bristow, Linda J.; Hutson, Peter H. (European journal of pharmacology, 2003)
It is well established that the NMDA receptor antagonists block hippocampal long-term potentiation and impair acquisition in the Morris watermaze task, although the role of individual NMDA receptor subtypes is largely unknown. In the present study, we compared the effects of (±)-CP-101,606, an antagonist selective for NMDA receptor NR1/NR2B subunit-containing receptors and the nonselective NMDA receptor antagonist MK-801, on acquisition in the Morris watermaze. Male hooded Lister rats were given 4 trials/day to find a fixed hidden platform submerged beneath the opaque water of the Morris watermaze. Twenty-four hours after the last acquisition trial, a ‘probe trial’ was conducted to assess the rat's spatial memory for the location of the hidden platform. Those rats treated with MK-801 (0.1 mg/kg, i.p.) 60 min prior to the acquisition and probe trials took significantly longer to find the hidden platform during training and spent significantly less time searching the platform's location during the probe trial than vehicle-treated rats. In contrast, 60-min pretreatment with (±)-CP-101,606 (60 mg/kg, p.o.), a dose that fully occupied hippocampal NR1/NR2B subunit-containing receptors, as determined by ex vivo NMDA receptor-specific [ 3H]ifenprodil binding immediately following watermaze experiments, had no effect on acquisition or the probe trial. These results suggest that antagonists selective for NR1/NR2B subunit-containing receptors may not impair spatial memory in rats in the Morris watermaze.